A Phenomenological Examination of Prisonization and the Psychological Effects of Incarceration - Bates, Wanda Lynn (2018)
Adjustment to prison culture may influence the development of psychological issues for some individuals and may contribute to the difficulties of reentry to society, potentially contributing to the high rates of recidivism. The purpose of this study was to explore prisonization and its potential psychological effects from the perspective of individuals who experienced it. The theoretical foundation used to guide this study was the constructivist self-development theory, which can be used to explain how individuals may or may not have been affected by their traumatic experience. The participants for this phenomenological study included 10 individuals who experienced incarceration to fulfill the purpose of exploring psychological effects that may have developed during incarceration. The open-ended research questions that were used in this study were designed to obtain a full description of the prisonization and postincarceration experience, including any psychological issues that may have resulted from the incarceration experience. The process of explicitation, which included bracketing, extracting unique themes, and summarizing, was used to analyze the collected data. The interviews suggested that symptoms of posttraumatic stress disorder may result from the prisonization experience. It is hoped that the results of this study may bring to awareness the psychological effects that can develop in some individuals during incarceration and may contribute to the difficulties of successful reentry to society